Nicotinic Acid Effects on Insulin Sensitivity and Hepatic Lipid Metabolism: An In Vivo to In Vitro Study - Blond, E.; Rieusset, J.; Alligier, M.; Lambert-Porcheron, S.; Bendridi, N.; Gabert, L.; Chetiveaux, M.; Debard, C.; Chauvin, M.-A.; Normand, S.; Roth, H.; de Gouville, A.-C.; Krempf, M.; Vidal, H.; Goudable, J.; Laville, M. (Hormone and Metabolic Research, 2014)
Our aim was to characterize the effects and the underlying mechanisms of the lipid-regulating agent Niaspan® on both insulin action and triglyceride decrease in 20 nondiabetic, dyslipidemic men with metabolic syndrome receiving Niaspan® (2 g/day) or placebo for 8 weeks in a randomized, cross-over study. The effects on plasma lipid profile were characterized at the beginning and the end of each treatment period; insulin sensitivity was assessed using the 2-step euglycemic hyperinsulinemic clamp and VLDL-triglyceride turnover by measuring plasma glycerol enrichment, both at the end of each treatment period. The mechanism of action of nicotinic acid was studied in HuH7 and mouse primary hepatocytes. Lipid profile was improved after Niaspan® treatment with a significant−28% decrease in triglyceride levels, a+17% increase in HDL-C concentration and unchanged levels of fasting nonesterified fatty acid. VLDL-triglyceride production rate was markedly reduced after Niaspan® (−68%). However, the treatment induced hepatic insulin resistance, as assessed by reduced inhibition of endogenous glucose production by insulin (0.7±0.4 vs. 1.0±0.5 mg/kg · min, p<0.05) and decrease in fasting hepatic insulin sensitivity index (4.8±1.8 vs. 3.2±1.6, p<0.05) in the Niaspan® condition. Nicotinic acid also reduced insulin action in HuH7 and primary hepatocytes, independently of the activation of hepatic PKCε. This effect was associated with an increase in diacylglycerol and a decrease in triglyceride contents that occurred in the absence of modification of DGAT2 expression and activity. Eight weeks of Niaspan® treatment in dyslipidemic patients with metabolic syndrome induce hepatic insulin resistance. The mechanism could involve an accumulation of diacylglycerol and an alteration of insulin signaling in hepatocytes.
Keywords: nicotinic acid; hepatic insulin-resistance; diacylglycerol; DGAT2 inhibition; euglycemic hyperinsulinemic clamp; VLDL-TG rate production